Antibacterial therapy of surgical sepsis: modern approaches, views, strategy and prospects - V. V. Vashchuk; V. P. Andriushchenko; T. P. Kyryk; M. I. Kushnirchuk; R. P. Baidala; A. Z. Ivanyshyn; T. V. Khomchenko (Клінічна хірургія, 2021)
Antibacterial therapy of surgical sepsis: modern approaches, views, strategy and prospects